The concept of freedom in the texts of Yashar Kamal play "The play (The Plate) as a model": عامر صباح نوري المرزوك (Al-Academy, 2021)
This research is concerned with studying (the concept of freedom in the texts of Yaşar Kamal the play), as the Turkish playwright (Kamal Yasar) is one of the contemporary playwrights who have been interested in and criticize society, and perhaps the concept of freedom in his texts took a different form, through his ability to renew and present his attempts to create A theatrical form different from his earlier writers in dealing with the life of the peasants and the oppression that went through them, as the researcher identified the problem of his research with the following question: What is the concept of freedom in the texts of Yashar Kamal? The research aims to define the concept of freedom in the texts of Yashar Kamal of the play, and the researcher (the concept of freedom) defines a procedural definition as: a method that the dramatic writer takes to express his own components, the issues of the individual and society, and carries with it a motivational goal that exposes ideologies and disturbs their will.While the second chapter dealt with three topics, the first concerned me with a study of the concept of freedom in human thought, and the second concerned me with the concept of freedom in the theatrical text, and the third studied the life of the writer Yashar Kamal and his references, while the third chapter included a full analysis of the play (the plate) as a model for the research, and the research concluded with the results , Among them:1. (Kemal) documented an important stage in the life of the Turkish peasant community, in a manner that approaches socialist realism.2. Kamal's interest has focused on the human subject as a vital starting point, from which he draws his dramatic material that contains the set of the essential components of his existence of choice, freedom and will, and the author approaches in building his ideas from the avant-garde drama book.